2022
DOI: 10.1097/jcma.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic drug liraglutide alleviates low muscle mass by inhibiting the expression of MuRF1 and MAFbx in diabetic muscle atrophy

Abstract: Background: Low muscle mass, that is, muscular atrophy, is an independent risk factor for type 2 diabetes mellitus (T2DM). Few studies investigated whether hypoglycemic drugs can alleviate low muscle mass and related mechanisms. Methods: This study recruited 51 type 2 diabetes mellitus (T2DM) patients, who were divided into two groups based on skeletal muscle index (SMI) evaluated by Dual-energy X-ray absorptiometry (DXA): the experiment group (n = 25, SMI < 7 kg/m 2 ) and the control group (n = 26, SMI≥7 kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…MAFbx and MuRF1 also play important regulatory roles in skeletal muscle atrophy and muscle injury [ 20 ]. Moreover, a study showed that liraglutide can alleviate low muscle mass by inhibiting the expression of MAFbx and MuRF1 in patients with diabetic muscle atrophy [ 21 ]. Western blot results showed that high glucose promoted the expression of MAFbx and MuRF1 in C2C12 myoblasts, and liraglutide could inhibit this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…MAFbx and MuRF1 also play important regulatory roles in skeletal muscle atrophy and muscle injury [ 20 ]. Moreover, a study showed that liraglutide can alleviate low muscle mass by inhibiting the expression of MAFbx and MuRF1 in patients with diabetic muscle atrophy [ 21 ]. Western blot results showed that high glucose promoted the expression of MAFbx and MuRF1 in C2C12 myoblasts, and liraglutide could inhibit this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…14 Besides, people with type 2 diabetes mellitus and lower skeletal muscle mass have lower glucagon-like peptide-1 levels, and treatment with liraglutide can alleviate muscle atrophy, which could have implications for muscle health in aging. 15 Among hopes for curative chronic disease therapies, caring for patients' quality of life through improving strength, function, and participation remains paramount. This requires recognizing sarcopenia not as an inevitable consequence, but as a critical target for intervention.…”
Section: Chenmentioning
confidence: 99%
“…14 Besides, people with type 2 diabetes mellitus and lower skeletal muscle mass have lower glucagon-like peptide-1 levels, and treatment with liraglutide can alleviate muscle atrophy, which could have implications for muscle health in aging. 15…”
mentioning
confidence: 99%
“…The domestic pig ( Sus scrofa ) is one of the main protein sources utilized by humans and an excellent research model for human muscle-related diseases [ 1 , 2 ]. The association between muscle insulin resistance and mitochondrial dysfunction is a common feature in the elderly and people who are susceptible to or have dominant type 2 diabetes mellitus [ 3 , 4 ]. The skeletal muscle is mainly composed of connective tissue and muscle fibers, which have the ability to regenerate and self-repair after injury [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%